Teachers’ Difficulties in Enhancing EFL Students’ Reading Motivation - lucky amatur rohmani (Universitas Lambung Mangkurat, 2022)
One of English teachers’ major concerns in teaching reading is students’ low reading motivation. Studies show that most of EFL learners are not highly enthusiastic when the teachers have them read English texts. Likewise, there have been limited efforts done by the teachers to address this problem. This study was therefore aimed to investigate the levels of students’ reading motivation, teachers’ difficulties in enhancing students’ reading motivation, and teacher effort to overcome the problems of motivating students to read. The participants were three EFL teachers and 12 students of junior secondary school in East Java. The data were collected through semi-structured interviews and observation. The result of semi-structured interview revealed that most of students had low reading motivation due to their understanding of difficult words in the reading text. Added to this, the major difficulty of teachers to enhance students’ reading motivation is related to increasing the interest, dedication and confidence of students in solving difficult vocabularies while reading English texts. This major difficulty reported by the teachers is in agreement with students’ report on their low reading motivation due to their limited vocabulary. Then, the result of observation showed that rewards had different effects on students’ reading motivation and the teachers should improve their efforts to enhance students’ reading motivation. Hence, several strategies such as reward, metacognitive reading strategy, reciprocal teaching method, reading aloud to improve students’ reading motivation were also suggested.